Curative outcomes following blinatumomab in adults with minimal residual disease B-cell precursor acute lymphoblastic leukemia. Issue 11 (18th September 2020) - Gökbuget, Nicola; Zugmaier, Gerhard; Dombret, Hervé; Stein, Anthony; Bonifacio, Massimiliano; Graux, Carlos; Faul, Christoph; Brüggemann, Monika; Taylor, Kate; Mergen, Noemi; Reichle, Albrecht; Horst, Heinz-August; et al.
Abstract: Minimal residual disease (MRD) is the strongest predictor of relapse in B-cell precursor acute lymphoblastic leukemia (BCP-ALL). In BLAST study (NCT01207388), adults with BCP-ALL in remission with MRD after chemotherapy received blinatumomab, a CD19 BiTE ® immuno-oncotherapy, 15 µg/m 2 /day for up to four 6-week cycles (4 weeks continuous infusion, 2 weeks off). Survival was evaluated for 110 patients, including 74 who received HSCT in continuous complete remission. With a median follow-up of 59·8 months, median survival (months) was 36·5 (95% CI: 22.0–not reached [NR]). Median survival was NR (29.5–NR) for complete MRD responders ( n = 84) and 14.4 (3.8–32.3) for MRD non-responders ( n = 23; p = 0.002); after blinatumomab and HSCT, median survival was NR (25.7–NR) ( n = 61) and 16.5 (1.1–NR) ( n = 10; p = 0.065), respectively. This final analysis suggests complete MRD response during blinatumomab treatment is curative. Post-hoc analysis of study data suggests while post blinatumomab HSCT may be beneficial in appropriate patients, long-term survival without HSCT is also possible.